The Impact of Internal Service Climate on Employeesa Job Satisfaction: With Reference to Commercial Bank of Ethiopia, Gedeo Zone (Global Journal of Management and Business Research, 2016)
It is of great interest to improve an organization's service quality by investigating the antecedents of customers' satisfaction in a dynamic, global business environment. Service industries try to compete by providing high-quality customer service via developing their internal service climate. Currently both industry and academia have shown a growing interest in the concept of internal service climate. Furthermore, internal service climate increases job satisfaction and reduces role stress. The main purpose of this study is to investigate the impact of internal service climate on employees' job satisfaction. The research design is a descriptive research. Both primary and secondary data were used in this research. A survey questionnaire with five point Likert scale was a main tool for gathering primary data about internal service climate effect on job satisfaction. 123 permanent employees were participated in filling the questionnaires. The researcher used censes sampling method.
Keywords: internal service climate (reliability; assurance; empathy; tangibility; and responsiveness); ANOVA; SPSS; likert scale